Implementation of Distance Learning at the Indonesian School Abroad in Singapore (SIS) - Muthia Izzatul Jannah; Shendi Agung; Arie Susanty (Southeast Asian Journal on Open and Distance Learning, 2025)
This study examines the implementation of Distance Learning (PJJ) at Indonesian Schools Abroad (SILN) in Singapore using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research identifies several challenges, including limited teacher-student ratios, technological barriers, and variations in student motivation. However, digital platforms such as Google Classroom and Zoom are considered effective in supporting learning, though improvements are needed in the quality of materials, delivery methods, and teacher feedback frequency. Findings indicate that most students benefit from the flexibility of time and technology access provided by PJJ. Nonetheless, challenges such as difficulty in maintaining focus during online learning, perceived heavy workloads, and mismatches between teaching materials and teachers' backgrounds persist. To optimize distance learning, teacher training, diversified teaching methods, improved teacher-student interaction, periodic evaluations, and active parental involvement are recommended. This study concludes that structured collaboration between educational institutions, parental support, and regular system improvements can enhance the quality of distance learning, provide better learning experiences, and meet students' holistic needs.